The impact of structured healthy lifestyle programs among type 2 diabetic patients in Pasir Puteh, Kelantan : a controlled trial. - Sulaiman, Suhaiza (2001)
Diabetes is a public health problem as it causes considerable amount of disability, premature mortality as well as demand on health care facilities. Increased in disease prevalence and its complications were mainly related to unhealthy lifestyle. A nonrandomised control trial was conducted with the aim of assessing the impact of structured healthy lifestyle programs amongst type 2 diabetic patients in Pasir Puteh, Kelantan. One hundred and forty type 2 diabetic patients from Selising Health Center (intervention group) and Gaal Health Center ( control group) were selected for the study. The intervention group was given a structured health education programs on self-care, dietary advise and exercise. Data was collected using a questionnaire, anthropometric measurements and blood samples for random blood sugar (RBS) and HbA1c. Statistical Package for Social Sciences (SPSS) version 10.0 was used to analyze the data. The . patients in both health centers had similar socio-demographic distribution (p value > 0.05). Most of them were Malays (99%), females (58.6 % intervention, 65.3 % control), married (74.3 % intervention, 86·7 % control), and non-smoker (66.7 % intervention, 72.9 % control). In the intervention group, their mean (SD) age and duration of diabetes was 55.4 (10.29) years and 5.6 (4.81) years respectively compared to the control group which was 54.2 (11.86) years and 5.4 (4.23) years respectively. The intervention packages effectively improved the knowledge and practice on healthy lifestyle among the patients as evidenced by improvement in HbAlc level (p < 0.05). Other variables (Body mass index (BMI), RBS and attitude) did not significantly improve (p>0.05). In conclusion, the structured healthy lifestyle programs which consisted of health education, dietary advise and physical activity have effectively improved the knowledge, practice and HbAle level of type 2 diabetes patients. The main challenge in management of these patients is however to sustain their healthy lifestyle.